Pengaruh Kualitas Pelayanan, Lokasi, dan Harga Terhadap Keputusan Pembelian LPG di PT. Jivantara Amaryz Sumbersongo - Taraka Karya Fadhel Kastara; Bayu Pramutoko; Rafikhein Novia Ayuanti (Jurnal Bisnis Islam dan Kewirausahaan, 2025)
This study aims to determine the effect of service quality, location, and price on LPG purchasing decisions at PT. Jivantara Amarys Sumbersongo. The method used in this study is quantitative descriptive. The population in this study were consumers of PT. Jivantara Amarys Sumbersongo who are still actively purchasing LPG until 2022, totaling 3285 consumers. The sample in this study were consumers at PT. Jivantara Amarys Sumbersongo who made purchases until November 2022, totaling 97 samples. The sampling technique used in this study was saturated sampling. Data analysis in this study includes validity test, reliability test, correlation test, multiple linear regression, coefficient of determination (R2), t test and F test. The results of this study are that: 1). service quality has a partial effect on purchasing; 2). Location has a partial effect on Purchasing decisions; 3). Price does not have a partial effect on Purchasing decisions  and 4). Service quality, location and price have a simultaneous effect on employee performance